Microsoft Office 2007 - Deborah Hinkle (McGraw Hill Higher Education, 2008)
The Hinkle, Professional Approach Series for Office 2007 offers an entirely new way of mastering Office 2007 applications. Using unique exercises from realistic business situations, this step-by-step approach is supported by a colorful graphics program. The series is ideal for students new to the world of computers, yet in-depth enough to challenge more savvy users. Each lesson contains up to 25 skill applications and each unit contains up to 5 skill applications that take students from simple to complex situations. Each of the individual application books are approved courseware for the MCAS Certificaiton exams. This "Learn by Doing" text is very hands on and provides a clear learning path with learning objectives so students see the skills they know and they ones they don't. This text also correlates with SimNet Online, our online training and assessment program for Office 2007